Dynamic-stiffening-induced aggravated cracking behavior driven by metal-substrate-constraint in a coating/substrate system. (28th February 2021) - Li, Guangrong; Tang, Chunhua; Yang, Guanjun
Abstract: Air plasma sprayed thermal barrier coatings (APS-TBCs) saw their wide application in high-temperature-related cutting-edge fields. The lamellar structure of APS-TBCs provides a significant advantage on thermal insulation. However, short life span is a major headache for APS-TBCs. This is highly related to the property changes and passive behaviors of the coatings during thermal service. Herein, a finite element model was developed to investigate the dynamic stiffening and substrate constraint on total spallation process. Results show that the stiffening accelerates the crack propagation of APS-TBCs. The driving force for crack propagation, which is characterized by strain energy release rate (SERR), is significantly enlarged. Consequently, the crack starts to propagate when the SERR exceeds the fracture toughness. In addition, the changing trends of SERR and crack propagation features are highly associated with temperatures. A higher temperature corresponds to more significant effect of stiffening on substrate constraint. In brief, temperature-dependent stiffening significantly aggravates the substrate constraint effect on APS-TBCs, which is one of the major causes for the spallation. Given that, lowering stiffening degree is essential to maintain high strain tolerance, and to further extend the life span of APS-TBCs. This understanding contributes to the development of advanced TBCs in future applications.